The Holocaust in the National Curriculum after 25 years. Issue 3 (3rd July 2017) - Pearce, Andy
ABSTRACT: This article provides a historical overview of the position of the Holocaust within the National Curriculum since 1991. Through close analysis of the five iterations of the curriculum, it traces changes and continuities in how teaching and learning about the Holocaust has been stipulated by successive governments. By contextualizing these with reference to shifts in England's Holocaust culture, it is shown that the National Curriculum has acted as a fulcrum for the evolution of Holocaust consciousness. However, it is also argued that many of the faults and failures, challenges and shortcomings within the National Curriculum are symbiotic and closely entwined with wider issues in Britain's Holocaust culture.